Taxonomy and SSU rDNA-Based Phylogeny of Two Heterotrich Ciliates (Ciliophora, Heterotrichea) Collected From Subtropical Wetlands of China, Including the Description of a New Species, Linostomella pseudovorticella n. sp. - Jin, Didi; Zhao, Xuetong; Ye, Tingting; Huang, Jie; Warren, Alan; Al-Farraj, Saleh A.; Chen, Xiangrui (Frontiers in Microbiology, 2021)
The Heterotrichea Stein, 1859 are a group of ciliated protists (single-celled eukaryotes) that occur in a wide variety of aquatic habitat where they play important roles in the flow of nutrients and energy within the microbial food web. Many species are model organisms for research in cytology and regenerative biology. In the present study, the morphology and phylogeny of two heterotrich ciliates, namely Linostomella pseudovorticella n. sp. and Peritromus kahli Villeneuve-Brachon, 1940 collected from subtropical wetlands of China, were investigated using morphological and molecular methods. Linostomella pseudovorticella n. sp. differs from its only known congener, L. vorticella (Ehrenberg, 1833) Aescht in Foissner et al., 1999, by having more ciliary rows (48–67, mean about 56 vs. 26–51, mean about 42) and its small-subunit (SSU) rDNA sequence which shows a 15-bp divergence. Although P. kahli has been reported several times in recent decades, its infraciliature has yet to be described. A redescription and improved diagnosis of this species based on a combination of previous and present data are here supplied. Phylogenetic analyses based on SSU rDNA sequences revealed that the genus Linostomella is positioned within Condylostomatidae and Peritromidae is sister to Climacostomidae with relatively low support. And the family Spirostomidae is the root-branch of the class Heterotrichea.